The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1088/1742-5468/2010/07/p07027
|View full text |Cite
|
Sign up to set email alerts
|

Critical interfaces of the Ashkin–Teller model at the parafermionic point

Abstract: We present an extensive study of interfaces defined in the Z 4 spin lattice representation of the Ashkin-Teller (AT) model. In particular, we numerically compute the fractal dimensions of boundary and bulk interfaces at the Fateev-Zamolodchikov point. This point is a special point on the self-dual critical line of the AT model and it is described in the continuum limit by the Z 4 parafermionic theory. Extending on previous analytical and numerical studies [10,12], we point out the existence of three different … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 49 publications
5
12
0
Order By: Relevance
“…One of these value, corresponding to a certain interface, was found in agreement with the one proposed on the basis of CFT computation in [9]. This scenario, which establishes for the first time a connection between geometrical objects and extended CFT, has been made particularly clear in [8] where the spin cluster interfaces of the Z 4 model model were studied.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…One of these value, corresponding to a certain interface, was found in agreement with the one proposed on the basis of CFT computation in [9]. This scenario, which establishes for the first time a connection between geometrical objects and extended CFT, has been made particularly clear in [8] where the spin cluster interfaces of the Z 4 model model were studied.…”
Section: Introductionsupporting
confidence: 84%
“…But, so far, the most important insights into this problem come from numerical measurements of the fractal dimensions associated to the spin interfaces for Z 4 and Z 5 spin models [7]. By measuring systematically all the different bulk and boundary spin interfaces, it was found that there is a limited number of possible values for the fractal dimension which can be understood on the basis of the classification of Z N conformal boundary conditions [8]. One of these value, corresponding to a certain interface, was found in agreement with the one proposed on the basis of CFT computation in [9].…”
Section: Introductionmentioning
confidence: 99%
“…• The case (1|234) is not understood for general couplings, but for g = 3/4 (where the AT model coincides with the integrable Fateev-Zamolodchikov Z 4 spin model), the associated operator satisfies a null-state equation in the Z 4 -parafermionic CFT, and is argued [13] The fractal dimension cannot be simply obtained from the CG analysis. However, based on the above exact values and Monte-Carlo simulations (in the region between Ising and Potts points), the following expression was proposed [9] for d f :…”
Section: Spin Interfaces In the Ashkin-teller Modelmentioning
confidence: 99%
“…There are different possibilities to define critical curves in the Ashkin-Teller model [17,18,19,20,21]. In the spin representation one can think about the domain walls between one spin and the other three, or the domain walls between two definite spins and the other two.…”
Section: Introductionmentioning
confidence: 99%